An evaluation of the City of Johannesburg's Igoli 2002 programme from 2003 to 2010 - Matebese, Zolani Loyiso Chukwuemeka Bantu,Musengi-Ajulu, Sandra (Rhodes University, Faculty of Commerce, Rhodes Business School, 2014)
Integrative Summary: Municipalities are the third level of government and are responsible for delivery of basic services to citizens. They carry the developmental mandate of government and are often the first point of interaction between government and citizens. Being at the front line of service delivery, the issue of fiscal stability of municipalities and their ability to deliver sustainable services is of grave importance (Carter & Ajam 2003). Unfortunately in a South African context most municipalities are not fiscally sustainable (Roos & Stander 2005). In a study of 142 South African municipalities, it was found that poor collection of outstanding debt and irregular or wasteful expenditure were the biggest causes of fiscal stress (Roos & Stander 2005). In fact, in 2004 the difficulties appear to have reached crisis level (Lubbe & Roussouw 2005). The fiscal situation within municipalities was so bad that the South African Local Government Authority (SALGA) implemented a unit specifically to assist municipalities that were at "crisis point" (Roos & Stander, 2005 p. 165). This research report focuses on the evaluation of Igoli 2002 which was a response to fiscal crisis within the City of Johannesburg metropolitan municipality when in 1997 the City of Johannesburg was declared insolvent. The research evaluated the long term sustainability of the Igoli 2002 programme to determine its success in addressing the issues of fiscal stress and crisis facing the municipality. The research also attempted to assess the applicability of international indicators of fiscal stress and crisis to the City of Johannesburg. The research evaluated the Igoli 2002 programme via a financial condition analysis, against international indicators of fiscal stress and crisis and against a logic framework detailing the goals of the programme. The research found that ultimately, the Igoli 2002 intervention implemented by the City of Johannesburg was successful in improving the fiscal position and sustainability of the City. In addition, indicators from predictive models of fiscal stress and crisis were found to be relevant to the City of Johannesburg.
Keywords: Municipal government -- South Africa -- Johannesburg; Local government -- South Africa -- Johannesburg; Expenditures, Public -- South Africa -- Johannesburg